2017
DOI: 10.1002/cncy.21896
|View full text |Cite
|
Sign up to set email alerts
|

Critical diagnoses in cytopathology: Experience at a large medical center

Abstract: Use of a code for critical cytopathology diagnoses was found to be occurring increasingly at the study health care system. Pathologists at the academic and community hospitals in the study institution used this code somewhat differently, reflecting the need to satisfy communication with clinicians in different practice settings. Nevertheless, the authors' experiences with using a code for critical diagnoses not only ensured timely patient care but also proposed a model that could be used by other medical speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…However, since the communication between pathologists and clinicians is frequently suboptimal and might result in misunderstandings, all reports should be conveyed in writing. Furthermore, semi-automated reporting via special codes can improve the quality of patient care [ 2 , 7 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since the communication between pathologists and clinicians is frequently suboptimal and might result in misunderstandings, all reports should be conveyed in writing. Furthermore, semi-automated reporting via special codes can improve the quality of patient care [ 2 , 7 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 1972, Lundberg first proposed the concept of critical value [ 1 ]. A critical value refers to a laboratory finding outside the normal range that might constitute an immediate health risk that would be otherwise difficult to detect [ 2 ]. It is also known as "critical diagnosis," "urgent diagnosis," and treatable, immediately life-threatening diagnosis."…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Nakhleh et al 11 found in a CAP survey of 1130 laboratories that only 75% had a written policy, and that no single diagnosis was regarded as critical by even half of laboratories. More recently, Xing et al 12 found increased use of a tracking code for cytology critical diagnoses in their laboratory information system among private hospitals within their medical system compared with the academic medical center, suggesting that clinicians in a private practice setting may desire more telephone communication than those in an academic setting, further supporting the need for institutional discretion. Along the way, a variety of editorial and review articles have also been published, which discussed the various issues involved with anatomic pathology critical values.…”
Section: Discussionmentioning
confidence: 99%
“…Xing et al investigated the quality assurance of critical diagnoses specific to cytopathology. The University of Pittsburgh Medical Center developed a semiautomated communication process for the communication of critical diagnoses known as MedTrak notification/CoPath tissue code TC66, which sent all final reports to the submitting physician via e‐mail and fax and notified him or her with a pager alert.…”
Section: Discussionmentioning
confidence: 99%